Implementation of an Opioid Reduction Protocol for Simple Outpatient Neurosurgical Procedures: A Single-Center Experience. Issue 6 (15th March 2020) - Eley, Nicholas; Sikora, Matt; Wright, Anna K.; Leveque, Jean-Christophe
Abstract : Study Design: Quality improvement with before and after evaluation of the intervention. Objective: To evaluate postoperative opioid utilization at a high-volume tertiary referral center following implementation of an opioid reduction protocol for simple outpatient neurosurgical procedures. Summary of Background Data: The opioid epidemic has been well-publicized both in the scientific and lay press over the last few years. As a response to this crisis many state-wide and national medical groups have sought to develop opioid prescribing guidelines for both acute and chronic pain states. Some guidelines have studied opioid prescribing in orthopedic procedures but have primarily limited their recommendations to simple outpatient orthopedic joint procedures. Although, it is not clear that these opioid prescribing reductions are directly translatable to neurosurgical procedures. Methods: We implemented an opioid reduction protocol geared towards the postoperative management for simple outpatient neurosurgical procedures and measured the effect on number of pills and total morphine equivalent dose (MED) prescribed, postoperative readmissions, refill requests, and conversion to long-term opiate use. Results: Our study population was 246 patients, with 109 patients in the pre-intervention (PRE) group and 137 patients in the post-intervention (POST) group. The vast majority of patients in both groups were discharged with an opioid prescription (93% PRE, 91% POST, P = 0.87). The POST group had significantly lower total discharge opioid medication quantity (52 tabs PRE, 27 tabs POST, P < 0.001), discharge day MED (51.3 PRE, 45.3 POST, P = 0.01), and total discharge MED (287 PRE, 149 POST, P < 0.001). Conclusion: A standardized discharge protocol for postoperative neurosurgery can lead to significant reductions in opioid discharge quantity without compromising patient safety or increasing the utilization of hospital resources through readmissions, refill requests, or clinic phone calls. This study provides an example of a feasible and effective discharge prescription regimen that may be generalizable to some of the most common outpatient neurosurgical procedures. Level of Evidence: 3 Abstract : The aim of this quality improvement study was to evaluate postoperative opioid utilization at a high-volume tertiary referral center. Our data demonstrates that a standardized discharge protocol for postoperative neurosurgery can lead to significant reductions in opioid discharge quantity without compromising patient safety or increasing the utilization of hospital resources.